Constitutionalism of European states: ensuring globalism in modern conditions - Панчишин, Руслан Ігорович; Панчишин, Р. І.; Панчишин, Руслан Игоревич; Panchyshyn, Ruslan I.; Боровицький, Олександр Андрійович; Боровицький, О. А.; Боровицкий, Александр Андреевич; Borovytskyi, Oleksandr A.; Рогач, Олександр Янович; Рогач, О. Я.; Рогач, Александр Янович; Rohach, Oleksandr Ya.; et al. (Editorial Primmate S. A. S., 2022)
Constitutionalism is a multidimensional phenomenon of state and socio-political life, which acquired different meanings and was filled with variable content in different periods of statehood development in connection with the formulation of constitutional ideas and principles and the formation of constitutional traditions, adoption of constitutions and their amendments. Today, ensuring the constitutionalism of European states has become an extremely essential issue. The work aims to analyze and study the provision of constitutionalism of European states in the modern conditions of globalism. Methodology: the historical method, the method of the generalization, the formal-legal method, method of analysis, comparative-legal method, method of social-legal experiment. Through the analysis of regulations of some European states and the views of some scholars, we can conclude that the modern idea of constitutionalization of the legal order is based on the postulates of constitutional theory and practical experience of democratic states.

Конституціоналізм – є багатовимірним явищем державного та суспільно-політичного життя, що набувало різних сенсів і наповнювалося варіативним змістом у різні періоди розвитку державності у зв’язку з формулюванням конституційних ідей і засад та становленням конституційних традицій, прийняттям конституцій та внесенням змін до них. Сьогодні надзвичайно важливим питанням стало забезпечення конституціоналізму європейських держав. Метою роботи є аналіз та дослідження забезпечення конституціоналізму європейських держав в сучасних умовах глобалізму. Методологія роботи: історичний, узагальнення, формально-юридичний метод, метод аналізу нормативних документів, статей та монографій, порівняльно-правовий метод, метод соціально-правового експерименту. Таким чином, за підсумками роботи, можна узагальнити, що cучасна ідея конституціоналізаціїправового порядку ґрунтується на постулатах конституційноїтеоріїі практичному досвіді розвитку демократичних держав.
Borovytskyi O., Rogach O., Pifko O., Stepanova T., Panchyshyn R. (2022) Constitutionalism of European states: ensuring globalism in modern conditions / // Amazonia Investiga. – Vol. 11. – Iss. 49. – Editorial Primmate S. A. S., 2022. – P. 47-54.
Keywords: constitutional law; constitutionalism; globalism; European state; national legal system; society; конституційне право; конституціоналізм; глобалізм; європейська держава; національна правова система; суспільство; Research Subject Categories::LAW/JURISPRUDENCE